Effect of ex situ Post-annealing Treatments on Sr2FeMoO6 Thin Films - Metsanoja M; Majumdar S; Huhtinen H; Paturi P (SPRINGER, 2022)
Magnetoresistive Sr2FeMoO6 thin films were grown by pulsed laser deposition at optimized deposition atmosphere and temperature. Films were then ex situ post-annealed in different atmospheres and by vacuum annealing at temperatures between 500 A degrees C and 1100 A degrees C. Ar and air annealed samples were destroyed by ex situ post-annealing treatment, due to formation and dominance of SrMoO4 impurity phase. X-ray diffraction showed no impurities and full texturation of vacuum and ArH2 (5%) annealed samples. Those samples showed also similar magnetic and magnetoresistive behavior like as-deposited sample. Neither magnetic, magnetotransport nor structural properties could be improved by ex situ post-annealing treatments.